1987
DOI: 10.1002/cm.970080308
|View full text |Cite
|
Sign up to set email alerts
|

Association of intermediate filaments with vinculin‐containing adhesion plaques of fibroblasts

Abstract: Double immunofluorescence staining of quail embryo fibroblasts with rabbit antibody to vinculin and mouse monoclonal antibody to vimentin revealed a coincidence between fluorescence patterns for cell-substrate focal contacts and intermediate filaments. Most of the vinculin-containing adhesion plaques coincided with the ends of vimentin-positive fibrils. This association was further corroborated by immunoelection microscopic observations of the cytoskeletons of quail and mouse fibroblasts using a platinum repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 26 publications
4
34
0
Order By: Relevance
“…For the latter reason we suggest the term vimentinassociated matrix adhesions (VMAs) for these adhesion sites. These may be comparable to the vimentin-associated focal contacts demonstrated by Bershadsky et al (1987) in quail embryo fibroblasts. We assume that plectin mediates the interaction of vimentin with these focal contact-like devices, based on its known vimentin-binding properties, its localization, and its function in linking other types of intermediate filaments to the cell surface (Wiche et al, 1982;Steinbö ck and Wiche, 1999).…”
Section: Discussionsupporting
confidence: 77%
“…For the latter reason we suggest the term vimentinassociated matrix adhesions (VMAs) for these adhesion sites. These may be comparable to the vimentin-associated focal contacts demonstrated by Bershadsky et al (1987) in quail embryo fibroblasts. We assume that plectin mediates the interaction of vimentin with these focal contact-like devices, based on its known vimentin-binding properties, its localization, and its function in linking other types of intermediate filaments to the cell surface (Wiche et al, 1982;Steinbö ck and Wiche, 1999).…”
Section: Discussionsupporting
confidence: 77%
“…Yet, a number of studies have indicated that in certain cells FCs show interaction with the vimentin cytoskeleton (Bershadsky et al, 1987;Gonzales et al, 2001). We have extended these observations.…”
Section: Discussionsupporting
confidence: 61%
“…fibroblasts vimentin IFs are connected to FCs (Bershadsky et al, 1987). Moreover, the idea that vimentin IFs are involved in modulating either the structure or function of FCs is also supported by observations of the organization of FCs along regions of cell-matrix interaction in vimentin-deficient fibroblasts (Eckes et al, 1998).…”
mentioning
confidence: 88%
“…It has been reported that vimentin colocalizes with adhesion plaques to stabilize the plaque. Adhesion plaque formation therefore influences cell-cell adhesion (Bershadsky et al, 1987;Burridge et al, 1988). In our present experiment, the structural organization of vimentin in endothelial cells by LMWH could therefore play an important role in the antiadhesion and antitransendothelial migration functions of LMWH.…”
Section: Discussionmentioning
confidence: 50%